Real-Time DNA Quantification of Nuclear and Mitochondrial DNA in Forensic Analysis. (August 2002) - Andréasson, Hanna; Gyllensten, Ulf; Allen, Marie
The rapid development of molecular genetic analysis tools has made it possible to analyze most biological material found at the scene of a crime. Evidence materials containing DNA quantities too low to be analyzed using nuclear markers can be analyzed using the highly abundant mtDNA. However, there is a shortage of sensitive nDNA and mtDNA quantification assays. In this study, an assay for the quantification of very small amounts of DNA, based on the real-time Taq-Man ® assay, has been developed. This analysis will provide an estimate of the total number of nDNA copies and the total number of mtDNA molecules in a particular evidence material. The quantification is easy to perform, fast, and requires a minimum of the valuable DNA extracted from the evidence material. The results will aid in the evaluation of whether the specific sample is suitable for nDNA or mtDNA analysis. Furthermore, the optimal amount of DNA to be used in further analysis can be estimated, ensuring that the analysis is successful and that the DNA is retained for future independent analysis. This assay has significant advantages over existing techniques because of its high sensitivity, accuracy, and the combined analysis of nDNA and mtDNA. Moreover, it has the potential to provide additional information about the presence of inhibitors in forensic samples. Subsequent mitochondrial and nuclear analysis of quantified samples illustrated the potential to predict the number of DNA copies required for a successful analysis in a certain typing assay.